Entrepreneurial Narrative Identity and Gender: A Double Epistemological Shift. (5th September 2014) - Hamilton, Eleanor; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> A double epistemological shift is proposed to challenge the enduring dominance of the discourse of entrepreneurial masculinity, which impedes our understanding of entrepreneurship. First, a reframing of the epistemological status of narrative supports philosophical and theoretical approaches to the constitution of narrative identity. Second, an epistemological shift to understand gender in entrepreneurship through the constitution of gendered identities in discourse is proposed. These shifts invoke the ontological dimension of narrative and contemporary theories of gender to understand entrepreneurial identity as co‐constituted and located in repertoires of historically and culturally situated narrative. This offers new theoretical and methodological possibilities in entrepreneurship.